HUBUNGAN OBESITAS DENGAN MIGRAIN PADA ORANG DEWASA - Andre; O siagian , Laura; Sinatra , Jadeny (Jurnal Kedokteran Methodist, 2021)
Background: Migraine is a headache that appears at a certain time accompanied by symptoms of throbbing, nausea, and vomiting that are often found in all age groups. There is two types of migraine syndromes, namely migraine with aura and migraine without aura. Migraine attacks usually last 4-72 hours. Migraine is a multifactorial disease or not only caused by one factor. Obesity is also a factor in migrains. Obesity is being overweight due to excessive accumulation of fat in the body. Methods: This research is using literature review method. Data obtained from secondary data using documentation techniques. Documentation of data which is done based on journals related to research variables. Conclusion: This literature review found that there is a relationship between obesity and migraine for adults.